Simplified methods for design of base-isolated structures in the long-period high-damping range. - Weitzmann, Ruediger
A recent trend in the design of base-isolated structures is the extension of the natural period and the incorporation of high damping. This paper shows that the existing simplified methods perform less accurately in this field of application, mainly due to inappropriate use of spectral data and insufficiently adjusted equivalent models. The paper proposes new period-dependent concepts to reduce pseudo-acceleration spectra and to transform these values into total accelerations with respect to the viscous damping ratio. The model of equivalent damping is adjusted to reflect several period-dependent effects. The estimation of the accelerations in MDOF systems is based on additional period shifts. All modifications are derived for a simplified linear approach based on eigenforms, and a non-linear approach based on pushover and capacity spectrum analysis. To illustrate observed problems and to demonstrate the capabilities of the proposed concepts, example structures are studied in detail. Furthermore, intensive statistical tests prove the effectiveness of the modifications in a wide parameter range and show considerable improvements over traditional approaches.
Keywords: Base isolation; Equivalent linear systems; Period dependency; Response spectrum reduction